An Economical and Portable Paper-Based Colorimetric Sensor for the Determination of Hydrogen Peroxide-Related Biomarkers - Zhang, Wei-Yi; Zhang, Hao; Yang, Feng-Qing (Chemosensors, 2022)
In this study, a paper-based sensor was developed for the detection of hydrogen-peroxide-related biomarkers, with glucose oxidase catalyzing as an example. Potassium iodide can catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine in the presence of hydrogen peroxide to colorize the paper-based biosensor detection area, which was imaged by a scanner, and the color intensity was analyzed by the Adobe Photoshop. Under the optimal conditions, the color intensity shows a good linear relationship with hydrogen peroxide and glucose concentrations in the ranges of 0.1–5.0 mM and 0.5–6.0 mM, respectively. The detection limit of hydrogen peroxide is 0.03 mM and the limit of quantification of glucose is 0.5 mM. Besides, the method was employed in measuring glucose concentration in fruit samples, and the spiked recoveries are in the range of 95.4–106.1%. This method is cost-effective, environmentally friendly, and easy to be operated, which is expected to realize the point-of-care testing of more hydrogen-peroxide-related biomarkers.